On the possibility of nanodispersed silicon dioxide synthesis by a coaxial magnetoplasma accelerator; Gas Discharge Plasmas and Their Applications (GDP 2015) - Nikitin D. S. Dmitry Sergeevich (Plasma sources and equme, 2015)
Заглавие с экрана.